Musculoskeletal tissue engineering: Adipose derived stromal cell implementation for the treatment of osteoarthritis. (July 2022) - Tevlin, R.; desJardins-Park, H.; Huber, J.; DiIorio, S.E.; Longaker, M.T.; Wan, D.C.
Abstract: Osteoarthritis (OA) is a progressive degenerative joint disease which results in chronic degeneration of articular cartilage and sclerosis of bone. While tendons and ligaments may heal to a limited extent, articular cartilage has poor intrinsic regenerative potential, and critical-sized bone defects and pathological fractures cannot regenerate spontaneously. OA represents a significant burden of disease globally, affecting 240 million people in the world. The objective of tissue engineering is to recapitulate the natural healing cascade and developmental process by transplanting stromal and progenitor cells which can act directly or indirectly. As the ultimate goal of regenerative medicine is to avoid in vitro expansion of cells and its associated complications, the adipose-derived stromal cell (ASC) is an attractive progenitor cell for tissue engineering for treatment of OA. While clinical studies are still in their infancy, ASCs together with novel scaffold materials represent promising treatment options for patients suffering from OA. How ASCs exert their regenerative potential is a topic of debate, whereby it may be a result of direct differentiation of ASCs into the desired regenerating tissue, and/or through paracrine activity. With the advancement of material science, it is increasingly possible to enhance engraftment of ASCs through the use of biomaterials or to direct progenitor cell fate by activating biophysical signals through designed material microstructures. There are currently over 180 completed or ongoing registered early stage clinical trials involving ASCs, with 17 completed studies reviewed herein detailing the use of ASCs in OA. In order for ASC therapy to become an "off-the-shelf" option for treating OA, several strategies are currently being explored such as ASC cryopreservation and use of allogeneic ASCs. Newer approaches, such as exosome therapy, allow for the use of acellular ASC-derived therapies and are also currently the focus of ongoing investigations.